Local energy policy and managing low carbon transition: The case of Leicester, UK. (January 2015) - Lemon, Mark; Pollitt, Michael G.; Steer, Steven
Abstract: National and local energy policies are implemented within a complex energy landscape that makes any evaluation of their impacts far from straightforward. Drawing upon a case study of Leicester this paper argues that the ability of local authorities to deliver significant energy savings within this landscape is questionable, albeit with other additional benefits being realised (e.g. job creation, community engagement). It examines existing domestic energy demand and multiple deprivation data for Leicester and neighbouring cities and combines this with a qualitative description of the transition process. The paper identifies the need for a more systematic analysis of how national energy policy translates to the local level and concludes that it is problematic even for a leading, pro-active and innovative local authority to have a statistically meaningful energy policy. Even where energy policies are favourable, carbon reduction is less easy to realise than other – more local - co-benefits and that in the light of significant financial and co-ordination constraints more attention needs to be given to how local communities can be more effectively supported in their desire to meet (or exceed) national targets. Highlights: This paper uses a case study of Leicester to explore the complex relationship between national and local energy policy. It suggests that even when a local authority is pro-active the delivery of carbon savings is problematic. Energy demand and deprivation data are analysed and the performance of three Midland cities compared. A qualitative analysis of the energy landscape is presented to help make sense of the quantitative analysis. A more systematic, cross-disciplinary, approach to the complex transition from national to local policy is argued for.